음료 분류별 일반적으로 사용되는 패키징 타입 및 형태적 특징 고찰 - 윤정우; Jung Woo Yoon (기초조형학연구, 2015)
물품의 특징적인 형태 혹은 실루엣은 매장에서 소비자가 더욱 쉽게 제품의 종류를 알아볼 수 있게 도움을 주는 요소 중 하나다. 소비자는 낯익은 형태적 특징으로 제품을 인지하고, 패키지에 쓰인 정보를 읽거나 라벨을 자세히 관찰하지 않고도 제품 카테고리를 분별하기도 한다. 음료 패키지의 경우 카테고리, 브랜드, 맛의 종류가 점점 늘어나고 있으며, 기술 및 신소재의 빠른 발달 으로 패키지 모양 또한 매우 다양하게 변화하고 있다. 수백 가지의 음료가 각기 다른 모양으로 경쟁하는 환경에서 카테고리 분야별 형태적 특징을 감안해 디자인 하는 것은 보다 쉽게 원하는 종류의 제품을 인지 해 구매로 연결될 수 있다. 브랜딩 프로세스에서 일관성이 중요한 것과 마찬가지로, 패키지디자인에도 제품 카테고리별 적절한 일관적특징이 적용되어야 한다. 기존의 특징이 적절히 함유된 새로운 패키지디자인은 현재와 같은 너무 다양해진 형태의 패키지들 사이에서 소비자가 품목을 더욱 쉽게 식별할 수 있도록 도움을 줄 수 있다. 본 논문은 현재 대중마트에서 유통되고있는 총 11가지 음료 카테고리의 형태적 특징 및 가장 익숙한 패키징 타입 (packaging type) 에 관한 연구이다. 연구의단계는 첫째, 효율적인 패키지디자인 및 패키지의 형태에 따른 이해에 관한 서적과 논문을 바탕으로 고찰하였으며, 둘째,간행본, 신문, 인터넷 포털사이트를 바탕으로 음료의 종류와 패키징 재질에 관한 조사를 하였다. 셋째, 음료 분류별 패키지 샘플들의 수집과 수집한 샘플들을 바탕으로 설문조사가 이뤄졌다. 마지막으로, 설문의 조사결과와 결과분석을 바탕으로 한 결론으로 구성되어있다. 본 논문에서 제시하는 카테고리 별 형태적 특징과 패키징 타입을 활용함으로, 향후 다양한 형태의 음료 패키지디자인 시도에서 소비자가 보다 쉽게 제품의 분류를 식별하도록 도움을 줄 수 있다. Physical attributes or silhouette of a product can work as a supportive element in finding the right product in the market environment. Consumers can recognize a product through its familiar physical attributes, that people understand the product``s category without having to check written information or going through package labels. There is constant increase in categories, brands and flavors of beverage products, and the forms of packages are becoming more diverse with the rapid development of new technologies and new materials. While hundreds of beverage products with unique physical forms compete with one another in market environments, designing a package with physical attributes of its own category can be easier for consumers to recognize the kind of product, which can ultimately lead to sales. Just like consistency is essential in branding process, there must be an appropriate amount of consistency applied to different types of categories in package design. With great deal of diversity in physical forms in product packages, it is easier for consumers to distinguish different lines of products if a new package design contains certain familiar physical qualities of past designs. This paper is a study of most distinct physical attributes and most familiar packaging types of 11 categories of beverage goods sold in mass markets. The process of the study is first, literary reviews of effective packaging design and comprehension through physical form of packages based on related books and papers. Second part include research of beverage product categories and different packaging types of beverages based on articles, newspapers and internet sites. Third part deals with collecting package samples and survey conducted utilizing the samples. Last part is conclusion of the study through analysis of the survey result. This study can be a supporting resource to explore diverse forms of beverage package designs, yet, recognizable of its category to consumers’ eyes, by utilizing physical characteristics and packaging types of each categories.